Analisis Kepastian Hukum dan Perlindungan Hukum Jamaah Umrah Mandiri (Berdasarkan Undang-Undang Nomor 14 Tahun 2025 Tentang Penyelenggaraan Ibadah Haji dan Umrah) - Adiyatma Firman Mahadi; Muh. Jufri Ahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the legal certainty regarding the regulations for independent Umrah based on Law Number 14 of 2025 concerning the Implementation of the Hajj and Umrah Pilgrimage and analyze the form of legal protection for independent Umrah pilgrims. The research used is normative legal research by applying three approaches, namely the statutory approach, the conceptual approach, and the case approach. The legal materials used consist of primary, secondary, and tertiary legal materials, which are analyzed prescriptively using legal interpretation, legal systematization, legal harmonization, and deductive reasoning. The analysis was carried out by applying the legal certainty theory of Gustav Radbruch, Utrecht, and Sudikno Mertokusumo as well as the legal protection theory of Philipus M. Hadjon. The results of the study indicate that the regulations regarding independent Umrah in Law Number 14 of 2025 have provided a legal basis for the implementation of the Umrah pilgrimage independently, thereby fulfilling the aspect of legal recognition as part of legal certainty. However, these regulations do not fully provide legal certainty due to vague norms and the lack of comprehensive provisions regarding state responsibilities, legal protection mechanisms, and dispute resolution for independent Umrah pilgrims. This study also found that legal protection for independent Umrah pilgrims consists of preventive and repressive legal protection, but its implementation still requires further regulation through implementing regulations to ensure effective legal protection.